As publicações no Journal of Organizational Behavior Management de 1999 a 2012 analisadas sob a ótica da análise do comportamento - Souza, Fernando Pomárico Barbosa (2014)
The aim of this study was to review the publications of the third decade of the Journal of Behavior Management (JOBM). We intended to replicate the study for the same purpose and compare the results obtained with those of the replicated study. Our interest was in analyzing whether the results of review of the third decade would be consistent, while keeping in mind the criteria proposed for applied research in behavioral analysis. One publication was selected for each year reviewed of the periodical, which consisted of 14 articles of applied research, encompassing the period from 1999 to 2012. The method used was based on criteria/dimensions for applied experimental research in behavioral analysis which were transformed into questions that served to guide the search in the reports of research. Seven criteria/dimensions were evaluated: Applied, Behavioral, Analytic, Technological, Conceptual, Effective and General. The results obtained indicated that the JOBM presented three purposes in its research studies, productivity, customer service and work safety, with productivity being the most evident. Most of the studies sought interventions that would achieve rapid results in meeting the needs of organizations and applications in the natural environment. Results indicated that trained observers were the most common source of data. A little more than half the studies were concerned with the reliability of the dependent variable 57%, and unsatisfactory numbers were found to verify the independent variable. In relation to the experimental designs used, only 50% of the studies used the intrasubject design. A large majority of the studies reported training for those responsible for introduction of the independent variable. The researchers reported the procedures in detail, but replication of the studies requires a greater description of the organizational configuration where the studies are conducted. The inclusion of cost-benefit measures and social validity should be found in a greater number of studies, as well as measures of generality. These results indicate that no dimension was fully served. The applied, behavioral, analytical, technological, conceptual and effective dimensions partially met the criteria for each dimension. Comparison with the review of the third decade of which the present study is a replication, indicated that not all the criteria could be compared. Discrepancies in the Applied and Analytic dimensions were found the reported aims were found in different percentages, and the same is true for the experimental designs that were identified in the publicationsnizational Psychology.